Advances and Challenges in Mucoadhesive Drug Delivery Systems: A Comprehensive Review - Krishna, P. V. V. Siva (Asian Journal of Pharmaceutics (AJP), 2024)
Pharmaceutical research has focused a lot of emphasis on the capability of mucoadhesive drug delivery systems to enhance patient compliance and therapeutic effectiveness. This thorough analysis examines the most recent developments as well as the ongoing difficulties in the discipline of mucoadhesive drug delivery. It explores the mechanics of mucoadhesion, emphasizing the complex relationships that exist among mucoadhesive polymers and mucosal surfaces. In addition, it covers the range of uses for mucoadhesive systems in oral, nasal, ocular, and vaginal delivery, among other modes of administration. The analysis sheds light on the design techniques used to maximize mucoadhesive formulations for better bioavailability, prolonged release, and targeted drug delivery. It also discusses the safety profiles and regulatory issues related to mucoadhesive products. The potential of mucoadhesive drug delivery systems to raise treatment effectiveness and patient compliance has attracted a lot of attention in pharmaceutical research. This thorough analysis examines the most recent developments as well as the ongoing difficulties in the discipline. It explores the mechanics of mucoadhesion, emphasizing the complex relationships that exist among mucoadhesive polymers and mucosal surfaces. In addition, it covers the range of uses for mucoadhesive systems in oral, nasal, ocular, and vaginal delivery, among other modes of administration. The analysis sheds light on the design techniques used to maximize mucoadhesive formulations for better bioavailability, prolonged release, and targeted drug delivery. It also discusses the safety profiles and regulatory issues related to mucoadhesive products. Even with the tremendous advancements, several issues including scalability, clinical translation, and formulation stability still need to be resolved. This study assesses mucoadhesive drug delivery systems critically, notes new developments, and suggests possible avenues to go over current obstacles and realize the full promise of these cutting-edge drug delivery platforms.